2005
DOI: 10.1037/1064-1297.13.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Performance and Autonomic Reactivity in Abstinent Drug Abusers and Nonusers.

Abstract: In this study the authors compared the performance of abstinent drug abusers (n = 21) and nonuser control participants (n = 20) in neurocognitive and emotional functions by use of the Rogers Decision Making Task, Gambling Task, Emotional Stroop, impulsivity continuous performance task (CPT), and vigilance CPT. Skin conductance (SC) and heart rate (HR) monitoring was synchronized with task performance. Groups showed similar performance for vigilance, impulsivity, and emotional interference; however, drug abuser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 84 publications
(100 reference statements)
0
25
0
1
Order By: Relevance
“…Social competence and risky decision-making may differ from these unrelated functions in terms of their complexity and the social context in which they occur or are triggered; the measures of impulsivity, delay of gratification, and emotional perception used in this study were without social context and elicited only very simple behaviors or reactions. Several other studies have found more complex neuropsychological and behavioral measures to more aptly characterize complex forms of psychopathology than simple measures (Fishbein et al, 2005a;Rogers & Robbins, 2001). Also, tobacco use was not predicted by any of these latent constructs, possibly due to the prevalence of smoking in this population and the overall attitude that smoking is not a "high-risk" behavior and is not generally used for its obvious psychoactive effects (although science has proved that attitude wrong on both counts for several decades).…”
Section: Discussionmentioning
confidence: 99%
“…Social competence and risky decision-making may differ from these unrelated functions in terms of their complexity and the social context in which they occur or are triggered; the measures of impulsivity, delay of gratification, and emotional perception used in this study were without social context and elicited only very simple behaviors or reactions. Several other studies have found more complex neuropsychological and behavioral measures to more aptly characterize complex forms of psychopathology than simple measures (Fishbein et al, 2005a;Rogers & Robbins, 2001). Also, tobacco use was not predicted by any of these latent constructs, possibly due to the prevalence of smoking in this population and the overall attitude that smoking is not a "high-risk" behavior and is not generally used for its obvious psychoactive effects (although science has proved that attitude wrong on both counts for several decades).…”
Section: Discussionmentioning
confidence: 99%
“…Although some findings indicate better performance, relative to nonabstinent substance users, following a period of abstinence (e.g., Bartzokis et al 2000), other research suggests that IGT impairment in polysubstance abusers is maintained even in abstinence, relative to normal controls (Fishbein et al 2005). In general, IGT performance among substance dependent individuals is impaired when compared to normal controls, and this impairment appears to last through a period of abstinence.…”
Section: Correlations With Other Executive Function and Decision Makimentioning
confidence: 96%
“…from infrequent punishment decks B 0 and D 0 or frequent punishment decks A 0 and C 0 (Dunn et al 2006), a selective preference for deck B 0 has been observed (Lin et al 2007;van den Bos et al 2006). Studies have shown a selective preference or avoidance for decks B 0 and D 0 (especially deck B 0 ) among clinical patients and in some normal control groups (Bark et al 2005;Fishbein et al 2005;Ritter et al 2004;Shurman et al 2005;Toplak et al 2005;Wilder et al 1998). Choice of decks B 0 and D 0 is explained by a preference for low frequency punishment and high frequency reward (ratio of 'wins' to 'losses'), but not on the basis of magnitude of reward-punishment (Shurman et al 2005).…”
Section: Introductionmentioning
confidence: 93%